The Effect Of Yoga Training Butterfly Pose, Child Pose, Cat And Cow Pose On The Intensity Of Primary Menstrual Pain (Dysmenorrhea) - Aprillia, Salwa Rizky; Wahyuni, S, Sri; Widiastuti, Dhias (Journal of Applied Health Management and Technology, 2023)
Dysmenorrhea is a gynecological problem that requires good, appropriate and comprehensive treatment. One of the treatments to reduce dysmenorrhea is by doing yoga. Objective: Knowing the effect of yoga training Butterfly Pose, Child Pose, Cat and Cow Pose on the intensity of primary menstrual pain (dysmenorrhea) in level I female students (first semester of the 2022/2023 academic year) at the Poltekkes Kemenkes Semarang Dormitory. The research method used True Experimental Design with Pretest - Posttest Control Group Design. The population in this study were level I students (first semester of the 2022/2023 academic year) at the Polytechnic Dormitory of the Ministry of Health Semarang who experienced dysmenorrhea and with Purposive Sampling technique obtained a sample of 30 students. The research instrument used a standardized Numeric Rating Scale (NRS) checklist. Data analysis using univariate and bivariate analysis. The results showed the initial measurement of primary dysmenorrhea intensity (mean experimental group = 6.13 and mean control group = 4.80), the final measurement of primary dysmenorrhea intensity (mean experimental group = 4.40 and mean control group = 5.53). There is a difference in the intensity of primary dysmenorrhea in the initial measurement and the final measurement of the data of the experimental group and the control group with a significance of <0.05. In conclusion, there is an effect of yoga training Butterfly Pose, Child Pose, Cat and Cow Pose on the intensity of primary menstrual pain (dysmenorrhea) in level I female students at the Poltekkes Kemenkes Semarang Dormitory. The existence of this research is expected to be able to add insight and knowledge related to yoga as one of the non-pharmacological treatments for primary menstrual pain (dysmenorrhea) and the application of yoga can be a solution to solving health problems, especially in female students who experience primary menstrual pain (dysmenorrhea). Dismenore merupakan masalah ginekologi yang membutuhkan penanganan secara baik, tepat dan komprehensif. Salah satu penanganan untuk mengurangi dismenore adalah dengan melakukan yoga. Tujuan : Mengetahui pengaruh training yoga Butterfly Pose, Child Pose, Cat and Cow Pose terhadap intensitas nyeri haid (dismenore) primer pada mahasiswi tingkat I (semester I tahun ajaran 2022/2023) di Asrama Poltekkes Kemenkes Semarang. Metode penelitian menggunakan True Eksperimental Design dengan Pretest – Posttest Control Group Design. Populasi dalam penelitian ini adalah mahasisiwi tingkat I (semester I tahun ajaran 2022/2023) di Asrama Poltekkes Kemenkes Semarang yang mengalami dismenore dan dengan teknik Purposive Sampling didapat sampel sejumlah 30 mahasiswi. Instrumen penelitian menggunakan checklist baku Numeric Rating Scale (NRS). Analisis data menggunakan analisis univariat dan bivariat. Hasil penelitian menunjukkan pengukuran awal intensitas dismenore primer (mean kelompok eksperimen = 6,13 dan mean kelompok kontrol = 4,80), pengukuran akhir intensitas dismenore primer (mean kelompok eksperimen = 4,40 dan mean kelompok montrol = 5,53). Ada perbedaan intensitas dismenore primer pada pengukuran awal dan pengukuran akhir data kelompok eksperimen dan kelompok kontrol dengan signifikasi < 0,05. Simpulan, terdapat pengaruh training yoga Butterfly Pose, Child Pose, Cat and Cow Pose (p value < 0,05) terhadap intensitas nyeri haid (dismenore) primer pada mahasiswi tingkat I di Asrama Poltekkes Kemenkes Semarang. Adanya penelitian ini diharapkan mampu menambah wawasan dan pengetahuan terkait yoga sebagai salah satu pengobatan non farmakologi terhadap nyeri haid (dismenore) primer serta penerapan yoga mampu menjadi solusi pemecahan masalah kesehatan terutama pada mahasiswi yang mengalami nyeri haid (dismenore) primer.